2004
DOI: 10.5194/angeo-22-1267-2004
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the ring current derived from magnetic field observations

Abstract: Abstract. Our examination of the 20 years of magnetospheric magnetic field data from ISEE, AMPTE/CCE and Polar missions has allowed us to quantify how the ring current flows and closes in the magnetosphere at a variety of disturbance levels. Using intercalibrated magnetic field data from the three spacecraft, we are able to construct the statistical magnetic field maps and derive 3-dimensional current density by the simple device of taking the curl of the statistically determined magnetic field. The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

40
205
3
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(254 citation statements)
references
References 40 publications
40
205
3
1
Order By: Relevance
“…There has been a symmetric ring current paradigm for years in which the ring current quickly becomes symmetric after the storm main phase, when ions drifting on open drift trajectories are trapped in closed drift paths, in response to the decrease in the convection electric field (Le et al, 2004). However, both the present work and Chen et al (1994Chen et al ( , 1997 challenge this paradigm that trapping of injected ions in closed paths may appear earlier in the main phase.…”
Section: Discussion and Summarycontrasting
confidence: 49%
See 1 more Smart Citation
“…There has been a symmetric ring current paradigm for years in which the ring current quickly becomes symmetric after the storm main phase, when ions drifting on open drift trajectories are trapped in closed drift paths, in response to the decrease in the convection electric field (Le et al, 2004). However, both the present work and Chen et al (1994Chen et al ( , 1997 challenge this paradigm that trapping of injected ions in closed paths may appear earlier in the main phase.…”
Section: Discussion and Summarycontrasting
confidence: 49%
“…In the conventional ring current pictiure, the "symmetric" ring current consists of trapped particles with closed orbit, while the particles with open convection paths create an "asymmetric" or partial ring current (Le et al, 2004). The D st index and SYM-H index are reliable indicators of the symmetric ring current strength, while the ASYM-H index measures the asymmetric ring current.…”
Section: Introductionmentioning
confidence: 99%
“…Le et al (2004) showed that the center position of the ring current also moves to larger distances from Earth with decreasing magnetic activity: it is located at about 5 Earth radii during storm-time periods and it extends to about 6 Earth radii far from the Earth during magnetic quiet times.…”
Section: Discussionmentioning
confidence: 99%
“…These values show the expected westward ring current around the equator. The morphology of the ring current system suggested by Iijima et al (1990) and Le et al (2004) partially closes in the ionosphere via up and down Region 2 FACs, and the ring current can extend from −65 to 65 • in latitude all over the evening and post-midnight sectors (Vallat et al, 2005). Considering the effect of the FACs on the accuracy of the current calculations, we focus here on the results in the equatorial plane (−30 to 30 • ).…”
Section: Introductionmentioning
confidence: 99%
“…It is understood in terms of the gradient and curvature drifts of energetic particles (∼1 keV to a few hundreds of keV), trapped in the geomagnetic field. Le et al (2004) examined the 20 years of magnetospheric magnetic field data from the ISEE, AMPTE/CCE, and Polar missions, and showed that there are two ring currents: an inner one flowing eastward at ∼3 R E , and the main westward ring current at ∼4-7 R E for all levels of geomagnetic disturbances. The ring current evolution is dependent on particle injections during geomagnetic activity and on loss mechanisms .…”
Section: Introductionmentioning
confidence: 99%